Analisis Faktor – Faktor Yang Mempengaruhi Keputusan Nasabah Dalam Pengambilan Kredit Pada Saat Sebelum Dan Selama Masa Pandemi Pada Bank Pembangunan Daerah Nusa Tenggara Timur - Setiyono, Taufiq Andre; Carvalho, Sarah Kristina Bunga Dacosta (Magister Manajemen STIE Bank BPD Jateng, 2024)
The purpose of this study was to test and analyze differences in customer decisions in taking credit before and during the pandemic which were influenced by interest rates, service quality, credit processes and income. This study uses primary data with a sample of 280 respondents. The sampling technique used in this research is accidental sampling. Data analysis was carried out using descriptive analysis with the help of SPSS 29. Based on this research, it can be seen that there are significant differences in customer decision making in taking credit during and before the pandemic which are influenced by interest rates, service quality, credit procedures and income.